Firm‐Sponsored General Training - Balmaceda, Felipe (Journal of Labor Economics, 2005)
This article analyzes firm and worker’s incentives to invest in general and specific training when these are separable in the production technology and wages are determined by the outside‐option principle. It is shown that firms pay for general training, while workers receive the full return on it, and firms and workers share both the costs and benefits of specific training. The case of delayed general training is also studied. When general training is delayed, it is shown that the strategic complementarity between specific and general training increases the worker’s incentives to invest in specific training.